The first fossil record of a giant horsetail (Equisetum, Equisetaceae) is from the Miocene of Patagonia, Argentina - Zamaloa, María del Carmen (2022)
A Miocene macroflora recovered from Ñirihuau Formation sediments exposed at Quebrada Vera site in northwesterern Patagonia, Argentina, is recorded and described for the first time. The assemblage is composed exclusively of free-sporing plants, mainly by Equisetum remains with subordinate occurrences of four fern morphotypes (represented by bi-, tri- and pinnate fronds). Equisetum imprints and molds include distinctive jointed stems with whorls of linear and basally fused leaves, numerous scars of lateral branches arranged in a radially symmetrical pattern situated at the nodes, and nodal diaphragms of up to 4 cm in diameter. The large size and regular branching of the stems link the fossils to the South American giant members of the genus and they probably represent a new fossil species. This is the first conclusive fossil record of a giant Equisetum worldwide, and consequently, it is biogeographically and evolutionarily relevant. The new findings attest that members of the giant horsetail clade were components of the Patagonian vegetation in the Miocene, implying that the age of the clade must predate that estimated from morphological and/or molecular data. The plant fossil assemblage represents part of a wetland community probably growing close to a riverside or lakeshore in coincidence with previous sedimentological estimates.